The minimally important difference for the Japanese version of the health assessment questionnaire in patients with rheumatoid arthritis in daily practice. Issue 3 (4th May 2017) - Shidara, Kumi; Nakajima, Ayako; Inoue, Eisuke; Hoshi, Daisuke; Sugimoto, Naoki; Seto, Yohei; Tanaka, Eiichi; Ikari, Katsunori; Taniguchi, Atsuo; Yamanaka, Hisashi
Abstract: Objective : To validate the minimally important difference (MID) of physical function using the Japanese version of the Health Assessment Questionnaire (J-HAQ) in a cohort of rheumatoid arthritis (RA). Methods : Patients who participated in a cohort study in both October 2008 and April 2009 were analyzed. Patients self-rated their change in overall status over 6 months using a 5-point Likert scale ("much better", "somewhat better", "same", "somewhat worse", or "much worse"). The MID for J-HAQ score was defined as the mean J-HAQ score change in patients who rated themselves "somewhat better". An effect size (ES) of 0.2–0.5 was considered to be suitable for MID. Results : A total of 4560 patients were analyzed. The mean (standard deviation [SD]) MID for J-HAQ score was −0.06 (0.29), corresponding to an ES of 0.08. As exploratory analysis, 1999 patients with a J-HAQ score ≥0.5 and 28-joint disease activity score (DAS28) ≥ 2.6 at baseline were assessed. The mean (SD) MID for J-HAQ score of these patients was 0.13 (0.01), corresponding to an ES of 0.21. Conclusions : The MID for J-HAQ score was 0.13 in patients with baseline J-HAQ score ≥0.5 and DAS28 ≥ 2.6. The MID for J-HAQ score was influenced by disease status and functional disability.